23. ANXIETY, DEPRESSION AND QUALITY OF LIFE IN PATIENTS WITH GASTROESOPHAGEAL REFLUX DISEASE (GERD): DEVELOPMENT AND VALIDATION OF VIETNAMESE VERSION (Vietnam Journal of Community Medicine, 2024)
Background: The Gastrointestinal Quality of Life Index (GIQLI) is a well-established questionnaire for the assessment of the quality of life (QOL) for GERD patients and The Hospital Anxiety and Depression Scale (HADS) is a screening tool for anxiety and depression, are widely used. Objective: Validation of the Vietnamese version of the GIQLI and HADS on patients with GERD at Military Hospital 175 in 2023. Methods: A descriptive cross-sectional study of GERD patients based on endoscopic findings. Internal reliability was assessed using Cronbach’s alpha coefficient and validity was evaluated by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Statistical analysis was performed with the Statistical Package for the Social Sciences, SPSS version 20.0 (SPSS Inc., Chicago, IL, USA) and AMOS version 20. Results: Among 173 participants, the male gender accounted for 60.7. Cronbach’s alpha of GIQLI, HADS Vietnamese version has good value (α is 0.835 and 0.78), showing that the questions are related to each other. The results of EFA and CFA analysis determine the structure of GIQLI including 5 factors and HADS consisting of 2 factors with the total variance explained at 68.851%, and 50.820%, respectively. Conclusion: The Vietnamese versions of the GIQLI and HADS questionnaires are valid and reliable. They can be applied to assess QOL and anxiety and depression in GERD patients in studies in Vietnam.
Keywords: Gastroesophageal reflux disease; GERD; GIQLI; HADS; validity.